Disziplingeschichte der Erziehungswissenschaft als Geschlechtergeschichte - Glaser, Edith; Andresen, Sabine (Jahrbuch Frauen- und Geschlechterforschung in der Erziehungswissenschaft, 2009)
Gender as a category has played and continues to play a decisive role in the formation, establishment and differentiation of the discipline of educational science. This connection has long been ignored, but Volume 5 of the Jahrbuch Frauen- und Geschlechterforschung der Erziehungswissenschaft (Yearbook Women's and Gender Studies in Educational Science) now deals with it systematically and unfolds new aspects of the history of discipline. In the contributions, the production of educational science knowledge is also analysed in the sub-disciplines and interesting theoretical accents and empirical findings are discussed in the presentation of new research projects.